2005
DOI: 10.1177/0022002704272830
|View full text |Cite
|
Sign up to set email alerts
|

Does Democracy Promote or Reduce Transnational Terrorist Incidents?

Abstract: This article studies the various mechanisms by which democracy affects transnational terrorism. New theoretical mechanisms are identified that either complement or encompass existing arguments. Different effects of democracy on transnational terrorism are assessed for a sample of about 119 countries from 1975 to 1997. Results show that democratic participation reduces transnational terrorist incidents in a country, while government constraints increase the number of those incidents, subsuming the effect of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
444
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 515 publications
(475 citation statements)
references
References 29 publications
18
444
8
Order By: Relevance
“…On the other hand, the findings accord with the stream of literature on the positive rewards of governance in mitigating terrorism activities, namely: theories of political access (Eyerman 1998) and empirical literature from perspectives of the rule of law (Choi 2010) and independence of the judiciary (Findley and Young 2011). As a point of synthesis, in the light of Li (2005), competing effects of good governance may not be apparent because: government constraints are not resulting in political deadlocks from checks and balances on the one hand and political participation reduces transnational terrorism on the other hand.…”
Section: 1 Nexus With the Literaturesupporting
confidence: 73%
See 3 more Smart Citations
“…On the other hand, the findings accord with the stream of literature on the positive rewards of governance in mitigating terrorism activities, namely: theories of political access (Eyerman 1998) and empirical literature from perspectives of the rule of law (Choi 2010) and independence of the judiciary (Findley and Young 2011). As a point of synthesis, in the light of Li (2005), competing effects of good governance may not be apparent because: government constraints are not resulting in political deadlocks from checks and balances on the one hand and political participation reduces transnational terrorism on the other hand.…”
Section: 1 Nexus With the Literaturesupporting
confidence: 73%
“…It follows that good governance institutions could also provide an enabling environment for aggrieved citizens to support or resort to terrorism as means to conflict resolution (Li 2005).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage in financial development established by Beck et al (2013) has been confirmed within the frameworks educational performance and economic growth by Agbor (2015). In essence, the logic underpinning this classification is that, the institutional web of formal rules, informal norms and enforcement characteristics within a legal system influence how terrorism is fought by means of institutional regimes and government quality (Li, 2005;Choi, 2010;Lee et al, 2013). Classification of countries within this category is based on information from La Porta et al (2008, p. 289).…”
Section: Determination Of Fundamental Characteristicsmentioning
confidence: 99%